Sosialisasi dan Pelatihan Peningkatan Pengetahuan dan Ketrampilan Produksi Home Industri Kerupuk Beras Merah di Desa Jatiluwih Tabanan, Bali - Sukanteri, Ni Putu; Pratiwi, Ni Putu Eka; Carina, Tiara (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2024)
Jatiluwih Village is one of the villages in Penebel District, Tabanan Regency, Bali Province. The main agrotourism capital of Jatiluwih Village is the agribusiness activity of red rice production, terraced rice fields and natural beauty. In creating various products that empower the community in Jatiluwih Village. The home industry aims to promote local products produced by the community in Jtiluwih Village. The aim of implementing the activity is to empower groups to become economically active groups through home industry productivity. Increase the knowledge and skills of group members in the field of production and marketing of the home industry of red sandalwood rice crackers. Developing the Jatiluwih Village PKK group to be economically independent. The activity method is carried out through socialization, training and mentoring in the PKK Group in Jatiluwih Village, Penebel District, Tabanan Regency, Bali Province. Community service activities carried out by PKK members in Jatiluwih Village, in an effort to develop the home industry, are as follows: Socialization of product hygiene shows that the knowledge of PKK members in Jatiluwih Village has increased by up to 100%. Training given to Jatiluwih Village PKK members in the use of grinding machines and mixers showed an increase of up to 80%. This shows that home industrial activities in Jatiluwih Village make it possible to increase production volume with training and mentoring.